GLYCOGEN SYNTHASE KINASE-3 BETA PROTEIN INHIBITION BY SELECTED PHYTOCOMPOUNDS IN SILICO - Varadharaj, Vanitha; Kandakatl, Naresh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Bioactive phytocompounds are a rich source of chemopreventive substance. In the present investigation, docking study was performed for the selected bioactive phytocompounds such as oleanolic acid, ecdysterone, betaine, stigmasterol acetate, and cinnamic acid to evaluate their affinity to glycogen synthase kinase-3 beta (GSK-3Î²) protein, a wound-healing biomarker. 2-chloro-5-[4-(3-chloro-phenyl)-2, 5-dioxo-2,5-dihydro-1h- pyrrol-3-ylamino]-benzoic acid was used as an inhibitor for GSK-3Î² with minimum binding energy (âˆ’31.5 kcal/mol). Methods: Molecular docking study was conducted using AutoDock 4.2 version and the visualization result using Discover Studio 4.5. Results: The docking analysis ranked the selected phytocompounds that have high theoretical scores to bind to the proteins. The binding mode of the phytocompounds that bound to all the target proteins with high affinity was studied. The simulation demonstrated that the protein-ligand complex stabilized by multiple hydrogen bonds (H-bonds) was preferentially formed at the catalytic site. The results highlighted in this study reveals that among the selected lead phytocompounds that docked into the active site of GSK-3Î², ecdysterone showed acceptable 6 H-bond interactions with residues LYS85, TYR134, ARG141, GLN185, ASP200, PRO136 when compared to the reference compound with 5 H-bond interactions. Conclusion: Thus, based on the docking score ecdysterone could be considered as a novel compounds that can be used for experimental studies for the inhibition of GSK-3Î² kinase. These results can be helpful for further design of novel GSK-3Î² inhibitors. Keywords: Phytocompounds, Molecular docking, Simulation, Receptor, Ligand, Inhibition.